From stigma to community’s discrimination : the experience of 16 former prisoners in Malaysia - Mohd Alif Jasni; Siti Hajar Abu Bakar Ah; Jal Zabdi Mohd Yusoff; Nini Syaheera Jasni; Khairiyah Md Shahid; Noralina Omar; Zaiton Azman (Penerbit Universiti Kebangsaan Malaysia, 2019)
Discrimination and stigma have been found to be one of the foremost factors that thwarted former prisoners to integrate well when released from prison. The effects of the discrimination that caused the former prisoners to be marginalized and disowned when to live in the original place. Rejection from the community of origin causes the former prisoner to fail to integrate smoothly and tends to re-engage in criminal life. In-depth interviews have been conducted on 16 former prisoners regardless of the type of offense committed. The analysis of the study has brought identification to the following three situations when respondents are in the community; (1) are excluded or not accepted by the neighboring residence, (2) neighbors do not want to know their presence, and (3) they are labeled with various embarrassing calls. These empirical findings can lead to the suggestion of a community-based program that can be implemented in bringing together former prisoners with the community as soon as they are released.